Structural Health Monitoring 2019 2019
DOI: 10.12783/shm2019/32365
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Ultrasonic Coda Wave Interferometry on a Real Bridge

Abstract: Urbanization becomes increasingly important in our modern life. This is undoubtedly a huge opportunity and challenge for construction industry. More and more bridges are constructed to improve the infrastructure and develop the economy. For more than a century, reinforced concrete bridges are the most common bridges due to its durability, relatively low maintenance cost and rapid construction. In general, concrete bridges are designed to ensure a service life of at least 100 years. However, mechanical and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…F T s of all transducer combinations are listed in Table 4 as F T 2. Comparing to F T 1, the value of F T 2 is much smaller and closer to the F T s found in another bridge in Wang et al 52 And F T 2 was estimated by the signals measured during the load test; thus, the temperature effect in the dV/Vs was eliminated by F T 2. The curves with circle markers represent the relative velocity variation without temperature compensation, and curves with triangle markers describe the temperature compensated dV/V.…”
Section: Load Testsupporting
confidence: 80%
See 1 more Smart Citation
“…F T s of all transducer combinations are listed in Table 4 as F T 2. Comparing to F T 1, the value of F T 2 is much smaller and closer to the F T s found in another bridge in Wang et al 52 And F T 2 was estimated by the signals measured during the load test; thus, the temperature effect in the dV/Vs was eliminated by F T 2. The curves with circle markers represent the relative velocity variation without temperature compensation, and curves with triangle markers describe the temperature compensated dV/V.…”
Section: Load Testsupporting
confidence: 80%
“…Example of temperature-compensated dV/V. dV/V curves measured by transducer S02E03 along three lines are 52 Bridge girder 36 m Environment 7 to 12 '20.02 Salvermoser et al 16 Bridge illustrated in Figure 15. When the truck left the bridge, dV/V returned to 20.009%, which was different from the initial state.…”
Section: Load Testmentioning
confidence: 99%
“…It can be easily installed in the structure during the construction before casting [26,29]. Moreover, a special installation method is developed allowing its installation on existing structures [25,28]. As the transducer is installed inside the structure, the interior of the structure is better monitored and the influence of near-surface changes is reduced.…”
Section: Transducer and Data Acquisition Systemmentioning
confidence: 99%
“…Existing studies have shown the high sensitivity of CWI to detect temperature change [17][18][19], stress variation [20,21] and damage [22,23] in small, laboratory size specimens. The CWI method has been also applied to large-scale specimens in outdoor environments [24] and successfully implemented on real structures [25][26][27]. Traditional NDT tools are normally used on the surface of the structure with limited penetration depth.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring and continuous observation of bridge structures has become an important part of the work of designers and scientists over the last few decades [ 1 , 7 , 15 , 17 , 26 , 27 , 28 , 29 , 30 ]. Both new structures and old ones require supervision for maintenance purposes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%